2024
DOI: 10.1111/jce.16235
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias in patients with bicuspid aortic valves

Michael Ghannam,
Boldizsar Kovacs,
Jackson Liang
et al.

Abstract: IntroductionBicuspid aortic valves (BAV) are the most common congenital heart defects and the extent of ventricular arrhythmias (VA) in patients with BAV is unclear. The objective of this study is to describe VAs and late gadolinium enhancement cardiac magnetic resonance imaging (LGE‐CMR) in patients with BAV.MethodsA total of 19 patients with BAV (18 males, age: 58 ± 13 years) were referred for VA ablation procedures. Ten patients had BAVs at the time of ablation, nine patients had prior aortic valve replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To the Editor, Ghannam and colleagues investigated the features of ventricular arrhythmia in patients with bicuspid aortic valve (BAV). 1 They demonstrated that ventricular arrhythmia in this cohort often originates from the peri-valvular area and those with BAV often had late gadolinium enhancement (LGE) and inducible ventricular tachycardia. Several concerns have been raised.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…To the Editor, Ghannam and colleagues investigated the features of ventricular arrhythmia in patients with bicuspid aortic valve (BAV). 1 They demonstrated that ventricular arrhythmia in this cohort often originates from the peri-valvular area and those with BAV often had late gadolinium enhancement (LGE) and inducible ventricular tachycardia. Several concerns have been raised.…”
mentioning
confidence: 79%
“…The authors' study included 10 patients with BAV who received no valvular interventions and 9 patients who had received aortic valve replacement for BAV. 1 The extra-valvular injury is staged according to the disease progression, ranging from left ventricle alone to mitral valve, left atrium, pulmonary vasculature, and right ventricle. 2 Thus, the severity of aortic stenosis may have a significant impact on the distribution and degree of myocardial injury as well as the burden of ventricular arrhythmia.…”
mentioning
confidence: 99%
See 2 more Smart Citations